Atividade osteoindutora da fotobiomodulação nos comprimentos de onda vermelho e infravermelho em modelo ex vivo de remodelação óssea - FURTADO, Guilherme Silva (2023)
Introduction: Photobiomodulation therapy (PBM) utilizes non-ionizing light at specific wavelengths to activate endogenous chromophores, modulating metabolic pathways, and inducing beneficial biological outcomes. Focused on wavelengths such as blue violet, green, red, and near-infrared, PBM has been applied in various therapeutic conditions, including brain injuries, wound healing, and bone regeneration. Objective: The study assessed the effects of PBM on bone remodeling in a physiological setting, using an ex vivo model of chicken embryonic femur. The research aimed to comprehend the molecular and cellular impacts of PBM on bone tissue and fill gaps in its efficacy and application protocols. Methodology: 5 fertilized chicken eggs (Gallus domesticus) were incubated in the Octagon 40 ECO egg incubator (Brinsea, UK) at a temperature of 37°C and 50% humidity. On the 11th day, the embryos were sacrificed, and the whole femurs were carefully dissected, removing soft tissues such as ligaments and adherent muscles. The femurs were then placed in Netwell culture inserts, which have a polyester membrane with pores of 440μm and 30mm in diameter (Corning, Arizona, USA). The femurs were cultured in 6-well tissue culture plates (Corning, Arizona, USA) containing 1mL of basal culture medium, composed of 1mL of αMEM, 100U/mL penicillin, 100μg/mL streptomycin, 2.5μg/mL amphotericin B, 50 μg/mL ascorbic acid 2-phosphate (all from Sigma). The femurs were divided into control and treatment groups (n=5). In the treatment groups, low-power diode laser irradiation was performed using red (660nm) and infrared (808nm) wavelengths. Continuous irradiation mode and a dose of 33.33J/cm2 were applied, corresponding to 10s, 100mW, so that each specimen received 1.0J of energy dose per irradiation. The femurs were irradiated four times during the 11 days of culture - immediately after dissection and 24 hours, 48 hours, and 7 days after the first irradiation. As a standardization measure, a distance of 1mm was defined between the laser source and the samples to avoid light dissipation and maximize energy absorption. The analysis was conducted on day 11, involving histochemical staining, histological analysis, and gene expression. Results: Irradiated femurs showed an increase in the mineralized area, suggesting higher osteoblastic activity at both wavelengths. Histological analysis indicated increased collagen deposition and maturation in the irradiated groups, with more pronounced effects in the infrared group. Gene expression revealed a significant increase in RUNX2 (Runt-related transcription factor 2) and SOX9 (SRY-like HMG [High-Mobility Group] Box 9), indicating enhanced osteochondrogenic commitment, along with a trend of reduction in SOST (Sclerostin). Conclusion: The results suggest that PBM, especially in red and infrared wavelengths, not only preserves bone structure but actively promotes bone formation under physiological conditions. This study provides a solid foundation for future investigations into the clinical application of PBM in bone regeneration.